Dialecticism and Occasionalism in Literary Texts (On the Example of Togay Murad's Works) (Eurasian Journal of Philology Science and Education, 2025)
The article describes the stylistic features of dialectism (dialectisms) and occasionalisms in the literary texts. Uzbeks in Uzbekistan live next to representatives of Turkic nation – Karakalpaks, Kazakhs, Kyrgyz, Turkmen. Living together with Turkic-speaking peoples and using languages ​​of different nationalities has greatly influenced on the Uzbek dialects of the regions, and the study of such words creates an opportunity to study the linguistic elements that are being forgotten in the vocabulary of the Uzbek language, obscure lexical-grammatical phenomena in the history of the language. In the article, stylistic features of dialectisms and occasionalisms used by the authors in the literary texts are taken as a research object. Classification of dialectism and occasionalism, dialectal and unusual derivative words - occasional lexical units are collected, selected and given with examples taken from Togai Murat's works. Various stylistic colors of words specific to dialects in the speaking style of the author and characters, creative skills in using new words created by means of word formation methods of folk words are highlighted in the article. Linguistic analysis, classification, description, comparative-historical, semantic-stylistic analysis methods are used in the work. The article is of particular interest to text linguistics researchers. Learning the lexical features of words in Uzbek dialects reflected in the works of Togai Murat opens the way to study the people's lifestyle, profession, and behavior and can provide valuable information for the lexicology and lexicography of the Uzbek language.Key words: vocabulary, dialectisms, occasionalisms, literary text, derivative words, word formation.